Novel Mucoadhesive Polymers - A Review - Mythri .G,K. Kavitha,M. Rupesh Kumar,Sd. Jagadeesh Singh (Journal of Applied Pharmaceutical Science)
The current article focuses on polymers used in mucosal delivery of therapeutic agents. The mucoadhesive drug delivery system is a popular novel drug delivery method because mucous membranes are relatively permeable, allowing for the rapid uptake of a drug into the systemic circulation and avoiding the first pass metabolism. Mucoadhesive polymers have been utilized in many different dosage forms in efforts to achieve systemic delivery of drugs through the different mucosa. These dosage forms include tablets, patches, tapes, films, semisolids and powders. The objective of this review is to study about novel mucoadhesive polymers and to design improved drug delivery systems.
Keywords: Novel drug delivery system, mucoadhesion, mucoadhesi